PENGARUH KUALITAS PELAYANAN PEMANDU WISATA TERHADAP KEPUASAN PESERTA KEGIATAN PENGENALAN DESTINASI WISATA DISPAREKRAF DKI JAKARTA - Ihsan Ramadhan; Rosita Anggraini (Media Bina Ilmiah, 2024)
Tour guide services in the introduction of tourist destinations indirectly affect the satisfaction of activity participants. Therefore it is necessary to study the influence of the quality of guide services on the satisfaction of participants in the introduction of destinations. The purpose of this study was to determine the influence and magnitude of the influence of the quality of tour guide services on participant satisfaction in the introduction of Disparekraf DKI Jakarta tourist destinations. The concept of service quality, satisfaction, and communication is used by the author as a guide in conducting research. The service quality variables consisting of Reliability, Responsiveness, Competence, Access, Communication, Security, Credibility, Direct Evidence and Participant Understanding have an effect on the participant's satisfaction with the introduction of destinations. The paradigm used in this study is positivistic with a quantitative approach. Respondents were participants in the introduction of destinations organized by the DKI Jakarta Province Tourism & Creative Economy Service, totaling 44 respondents using a saturated sampling technique. Collecting data in this writing using a questionnaire technique and literature study then analyzed with Likert scale analysis, validity and reliability test, linear regression analysis, t test analysis, and r test analysis. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Based on the research results, it is known that the t table value is obtained where N = 44 and sig. 0.05 of 2.015. From the results of the t test analysis, it is known that the t-count is 8.257 > 2.015 (t-table) and sig. of 0.000 <0.05. From these results it can be said that the Quality of Tour Guide Services has a positive and significant effect on Participant Satisfaction. From the table it is known that the r-square value is 0.619 or 0.619X100 = 61.9%, meaning that the total influence given by the Quality of Tour Guide Service variable on Participant Satisfaction is 61.9%. While the remaining 38.1% is influenced by other variables outside the variables studied. This means that there is a strong influence between the quality of tour guide services on the satisfaction of participants in the introduction of tourist destinations.